Research Trends on Critical Thinking Skills Based on the Scopus Database - Wulandari, Indah; Julianto, Julianto; Hasyim, Faiz; Admoko, Setyo (Studies in Physics Teaching and Learning, 2025)
Critical thinking is the ability to think clearly and reflectively by examining one’s own thought processes as well as those of others. It also represents an attitude of questioning phenomena that go beyond personal experience and considering problems from multiple perspectives. Developing critical thinking skills requires continuous efforts to improve the quality of education in facing the demands of the modern era. Therefore, this study was conducted to map and evaluate research on critical thinking through bibliometric analysis. The aim is to analyze publication trends on critical thinking skills from 2012 to 2022, visualize research patterns using VOSviewer software, and identify how researchers, institutions, and countries contribute to this field. From a total of 1,063 documents, Indonesia emerged as the leading contributor with 557 publications, positioning the Indonesian University of Education as the top institution and Zubaidah, S. as the most productive author. The visualization of research trends revealed three major clusters and one minor cluster, which cover: (1) factors influencing critical thinking skills, (2) training processes in critical thinking, (3) critical thinking disposition, (4) research methods on critical thinking, and (5) instruments for assessing critical thinking. The findings of this study are expected to help researchers identify global trends in critical thinking research. Furthermore, the results provide valuable insights for strengthening the development of critical thinking in physics education, particularly in designing learning models that foster problem solving, logical reasoning, and conceptual understanding.